Synthesis, Crystal Structures and Anticancer Activity of Pt(II) Complexes with Two Sterically Hindered 2-Methylpyridine Groups as The Carrier - Yu, Yao; Xie, Ming-Jin; Liu, Wei-Ping; Ye, Qing-Song; Chen, Xi-Zhu; Chang, Qiao-Wen (Asian Journal of Chemistry, 2010)
A series of novel platinum(II) complexes with two sterically hindered 2-methylpyridine groups as the carrier, cis-[Pt(2-methylpyridine)2X2] (X = Cl– (1), oxalate (2), malonate (3), 1,1-cyclobutane dicarboxylate (4), 3-hydroxy-1,1-cyclobutane dicarboxylate (5), were synthesized and characterized by elemental analysis, IR, mass spectra and 1H NMR spectra. The crystal structures of complexes 3-5 were further determined by X-ray single crystal diffraction. The two pyridine moieties adopts an almost perpendicular orientation relation to the platinum coordination plane and the two CH3 groups are located above the coordination plane, approaching Z axis. These structural arrangements produce greater steric hindrance for ligand substitution reactions. Unfortunately the complexes do not show any significant anticancer activity against A549, A549/ATCC and SGC-7901 cancer cell lines, possibly due to the fact that they lack hydrogen atoms on N-donors.